Exploring Teacher Competency and Work Motivation as Catalysts for Performance - Nurhidayat, Pimas Rajab; Jamaludin, Asep; Nandang, Nandang (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2024)
This study aims to determine the effect of teacher competence and work motivation on teacher performance. This study uses a quantitative descriptive approach. The population in this study were all teachers, deputy principals and principals at MTs Miftahul Huda Tegalwaru Karawang with a total of 43 people. Semple used in this study used saturated semple with 43 respondents. The data source used in this study using primary data obtained from distributing questionnaires to respondents. Based on the results of the study, it is known that the competency variable has no significant effect on the teacher performance variable partially while the motivation variable has a significant effect on the teacher performance variable partially. and the competency and motivation variables simultaneously have a significant effect on the teacher performance variable.